Beowulf: A Translation - Meyer, Thomas, 1947- (Book collections on Project MUSE., 2020)
A stunning experimental translation of the Old English poem "Beowulf," over 30 decades old and woefully neglected, by the contemporary poet Thomas Meyer, who studied with Robert Kelly at Bard, and emerged from the niche of poets who had been impacted by the brief moment of cross-pollination between U.K. and U.S. experimental poetry in the late 1960s and early 1970s, a movement inspired by Ezra Pound, fueled by interactions among figures like Ed Dorn, J.H. Prynne, and Basil Bunting, and quickly overshadowed by the burgeoning Language Writing movement. Meyer's translation -- completed in 1972 but never before published -- is sure to stretch readers' ideas about what is possible in terms of translating Anglo-Saxon poetry, as well as provide new insights on the poem itself. According to John Ashberry, Meyer's translation of this thousand-year-old poem is a "wonder," and Michael Davidson hails it as a "major accomplishment" and a "vivid" recreation of this ancient poem's "modernity."